1993
DOI: 10.1021/bi00054a006
|View full text |Cite
|
Sign up to set email alerts
|

One- and two-dimensional NMR characterization of oxidized and reduced cytochrome c' from Rhodocyclus gelatinosus

Abstract: 1D and 2D NMR spectra of both the reduced and oxidized forms of cytochrome c' from Rhodocyclus gelatinosus have been recorded. The analysis of the pH dependence of the 1H NMR spectrum of the ferric form has been performed, and two main ionizing groups have been identified. By comparison of the pH dependence of the available spectra of cytochromes c', an ambiguity remaining from previous studies on related cytochromes c' has been solved. By means of 2D spectra, an assignment of all the paramagnetically shifted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
55
2

Year Published

1993
1993
2016
2016

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(61 citation statements)
references
References 49 publications
4
55
2
Order By: Relevance
“…The methyl T, values in the cyanide derivatives of iron(II1) metmyoglobin and peroxidases are about 100 ms and 50 ms, respectively, i.e. of the same order as those found in reduced Mb and in reduced cytochrome c' [34]. This means that the electron-relaxation times of high-spin iron(I1) have to be approximately six-times smaller than in low-spin iron(1II) owing to the different S values [45].…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…The methyl T, values in the cyanide derivatives of iron(II1) metmyoglobin and peroxidases are about 100 ms and 50 ms, respectively, i.e. of the same order as those found in reduced Mb and in reduced cytochrome c' [34]. This means that the electron-relaxation times of high-spin iron(I1) have to be approximately six-times smaller than in low-spin iron(1II) owing to the different S values [45].…”
Section: Discussionsupporting
confidence: 62%
“…Reduced cytochrome c' species. which have a histidine as axial ligand, show three CH, signals upfield and one downfield [34,[47][48][49]. In reduced Mb from different sources [19] two CH, signals are found downfield and two are hidden under the diamagnetic envelope.…”
Section: Discussionmentioning
confidence: 99%
“…2, where it can be seen that unique resonances, most of which have intensities corresponding to one or three protons, are observed that are similar in general appearance to those of previously studied high-spin Fe(III) proteins (36), especially horseradish peroxidase (36,44,45) and cytochrome cЈ (36,(46)(47)(48). The assigned heme methyl and propionate resonances of NP2 (34) and its distal pocket mutants are labeled.…”
Section: Proton Nmr Spectra Of the High-spin (S ‫؍‬ 5͞2) (No-free) Fomentioning
confidence: 62%
“…Early magnetic susceptibility measurements on cytochromes c 0 were interpreted with a physical model that implied a thermal equilibrium between the low spin (S = 1/2) and the high-spin (S = 5/2) states [22]. Later, optical [23], near infrared [24], near infrared MCD [25], Mössbauer [26], and NMR [27][28][29][30][31][32] data suggested that cytochrome c 0 is substantially high-spin (S = 5/2) at neutral pH. In contrast to both hypotheses above, EPR [33][34][35][36][37][38][39][40], Mössbauer [41], optical [42], NMR [43] and resonance Raman [44] results were interpreted with the hypothesis of a quantum mechanical admixture of a high-spin (S = 5/2) and an intermediate spin (S = 3/2) state.…”
Section: Introductionmentioning
confidence: 99%